Das verbas locatícias nos contratos de shopping center e a incidência da cláusula de raio - Souza, Georgia Moraes de Souza (2013)
This paper demonstrates the importance of the relationship between entrepreneurs and shopkeepers, and the need to establish standards governing the balance of this relationship. The malls represent the great center of concentration regarding retail activities in our country, a fact that reveals the importance of socio-economic sector. The analysis of Shopping Centers’ contracts conducts its legal complexity, its special characteristics and the balance in the relationship, especially the funding and the inclusion of radius clauses. Therefore, it seeks to analyze the origin of the establishment of Shopping Centers, through legal characteristics and peculiarities present in this enterprise, ranging from the Lease Agreements to the most controversial aspect involving such legal business: the money levied on lease agreements, with emphasis on the radius clause, also called territorial exclusivity clause and the balance between the parties. With the advent of the New Civil Code there was a significant change in the rules of interpretation of contract law, in order to ensure, through the principles and general terms, the balance in private affairs rather than the absolute freedom of negotiation. The Lease Law No. 8.245/91 legitimizes relations between shopkeepers and entrepreneurs and employment of its procedures for evaluation of the rental. The theme is hereby studied and based on principles, doctrines and jurisprudences facing the subject, presenting insights favoring the legitimacy of the studied compensation, supported under the preponderance of free pact, and also to those who understand the possibility of its modification. Through the research conducted, it was possible to infer that, notwithstanding the fact that the discussion is ongoing, the unconditional freedom inherent to Shopping Center contracts needs to be curtailed in favor of the possibility of state intervention to achieve the contractual balance. This is because the systematic belongs to the contractual universe and must not admit any exceptions if not the goal to protect the balance between contractors